استدراكات العلامة إبراهيم المارغني على نظم الدرر اللوامع من خلال كتابه النجوم الطوالع -جمعا ودراسة- - بحري, محمد (University of Eloued جامعة الوادي, 2020)
" هذا البحث عبارة عن جمعٍ لاستدراكات العلامة إبراهيم المارغني التونسي المتوفى سنة 1349 هجريّة على نظم الدّرر اللّوامع في أصل مقرإ الإمام نافع للعلامة أبي الحسن محمد بن علي الرباطي المعروف بابن برّي المتوفى سنة 731 هجرية، التي ضمّنها كتابه الماتع الموسوم بـ: ""النّجوم الطّوالع على الدّرر اللّوامع في أصل مقرإ الإمام نافع"" فشرعت فيه أولا بدراسة نظرية، قمت فيها بالتعريف بالاستدراكات، والعلاّمتين ابن برّي صاحب نظم الدّرر، وشارحه المارغني، كما عرفت بمنظومة الدّرر اللّوامع وبشرح المارغني عليها المسمى بـ: ""النّجوم الطّوالع""، فكانت كتمهيد لصُلبُ الموضوع، الذي عرضتُ فيه استدراكات المارغني على نظم الدّرر - حاويا سبعة وعشرون استدراكا منها أربعة عشر تعقبا - وقمت بدراستها، مقسمة على جزئين، الأول: للاستدراكات، والثاني: للتعقبات، مع ترتيب كل منهما على حسب أبواب المنظومة، وقدمت لكل جزء بتمهيد أبين فيه صيغ كل من الاستدراكات والتعقبات ومنهج المارغني في عرضهما، ودرست هذه الاستدراكات والتعقبات دراسة تحليلية نقدية، مذيلا كل دراسة بنتيجة. وتممت هذا البحث بخاتمة حوت نتائج أهمها: أن أغلب استدراكات الشيخ إبراهيم المارغني مفيدة وصائبة إلا أن الناظم ترك ذلك قصد الاختصار والاقتصار على أهم الأوجه والمسائل، وأغلب تعقباته لا تخلو من تعقيب أو توجيه وجيه لكلام الناظم. وبعد ذكر النتائج ذيلت الخاتمة بتوصيّات أقترح فيها مواضيع لطلاب العلم من خلفنا أن يقوموا بدراستها."This Search is a collection of a criticism of the Tunisian scientist Ibrahim Marighni who died in 1943H, on the ""nodm al dorar al lawami"" in the provenace of Imam Nafa for the scientist Abu alhassan ali ibn mohammed al rebati, and also known as ""ibn barri"" who died in 731H, wich was mentioned in his book ""al nojoum al tawala ala al dorar fi asli makrai Imam nafa"", first, I started it with a theoretical study in wich I introduced the definition of the ""trackbacks"", and the two scientyists Ibn barri owner of ""system of al dorar"", and its explainer Al Marighni, and also I introduced the system of al dorar al lawama, and Marighni explanation on it ""al nojoum al tawala"", it was an introduction for the main subject, wich I introduced the Mareghni corrections on the system of al dorar –containing twenty seven criticism, including fourteen correction- and I studied it, divided on two, first: in the criticism and second: in the corrections, which was organized according to the order of the system, and I presented for each part where I showed the formulas of both corrections and criticism and their Mareghni method presentation, and I also relied on the analytical critical study, closing each study with a conclusion. This research was completed with a conclusion that contains the most important results: that most of Shikh Ibrahim Al-Marighni assessments are useful and correct, but Ibn Barri gave up on that in order to shorten and limit the most important aspects and issues, and most of his criticism aren’t without comments and directions for Ibn Barri speech. After mentioning the results, the conclusion was followed by recommendations in wich i suggest topics for the students behind us that they shout study"
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: استدراكات - إبراهيم المارغني - نظم الدرر اللوامع - النجوم الطوالع; collection of a criticism - Ibrahim Marighni - "nodm al dorar al lawami- al nojoum al tawala